Recent advances in transition metal-catalyzed C(sp)-H nitration - Song, Li-Rui; Fan, Zhoulong; Zhang, Ao (Organic & biomolecular chemistry, 2019)
Nitroaromatic compounds play an important role in organic synthesis, medicinal chemistry and chemical industry. Among the recently reported synthetic methods to access nitroarenes, transition metal-catalyzed C(sp 2 )-H activation/nitration has become one of the most attractive protocols, showing high regioselectivity, excellent functional group tolerance and step-economy. In this review, we discuss advances in direct C(sp 2 )-H nitration for the synthesis of nitroaromatic compounds and mechanistic insights over the past decade. We hope this will provide valuable information for researchers interested in the rapidly developing field of metal-catalyzed C(sp 2 )-H nitration. This review updates advances of direct C(sp 2 )-H nitration for the synthesis of nitroaromatic compounds and the mechanisms during the past decade.